Effects of Three Common Choral Performance Movement Conditions on Acoustic and Perceptual Measures of Choral Sound. (October 2020) - Grady, Melissa L.; Gilliam, Tianna M.
The purpose of this investigation was to examine the effects of three commonly observed choral singer performance conditions (no movement, slight swaying, full-body swaying) on acoustic and perceptual measures of choral sound. We audio recorded an established university choir ( N = 29 singers) performing a memorized piece while viewing the same conductor video and participating in one of the three performance conditions. We analyzed data through long-term average spectrum (LTAS), overall pitch deviation, and singer and listener (singer-listeners, expert-listeners) perceptions. LTAS results showed significant differences ( p < .001) in spectral energy between all three conditions. The full-body swaying condition averaged a noticeable difference of 2.50 dB across the spectrum when compared to the other two conditions. Pitch analysis indicated the least overall pitch deviation during the slight swaying condition (−27.67 cents) and the most pitch deviation during the no-movement condition (−58.31 cents). Results indicated singer and singer-listener preferences for the full-body swaying condition and expert-listener preferences for the slight swaying condition. We discuss results in terms of future research and practical application for choral music educators.